Comparison of polymer types on physical evaluation of in situ ophthalmic gel preparations: A Review - Putra, Hasan Etanov; Zahra, Aliya Azkia; Aini, Kania Nurul; Rafifa, Muthia; Maulida, Verin Sakinah; Sabrina, Lina Maisa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The development of temperature, pH, and ion-responsive in situ ophthalmic gels aims to enhance drug retention and release efficacy in the eye. Polymers such as Poloxamer (thermosensitive), Gellan Gum (ion-sensitive), and Carbopol (pH-sensitive) exhibit adaptive gelation mechanisms suited to ocular physiological conditions. Poloxamer forms a gel at body temperature, prolonging drug contact duration, while Gellan Gum creates a stable gel network through ionic interactions with lacrimal fluid, increasing viscosity and extending drug release. Carbopol, which transitions into a gel at neutral pH, provides optimal viscosity stability in the ocular environment. This study employs a literature review method, gathering data from indexed journals and scientific publications over the past 10 years. Evaluation results indicate that a combination of Gellan Gum and Methacrylated Gellan Gum at a concentration of 0.6% w/v yields the highest viscosity and encapsulation rate, with a contact time of up to 8 hours, making it an excellent formulation for long-term ophthalmic applications. This paper highlights the significant potential of in situ gels as drug delivery systems, optimizing ophthalmic therapy by enhancing drug viscosity and encapsulation stability.